2022
DOI: 10.1101/2022.02.15.480596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recombinant production of growth factors for application in cell culture

Abstract: Culturing eukaryotic cells has widespread applications in research and industry, including the emerging field of cell-cultured meat production colloquially referred to as cellular agriculture. These applications are often restricted by the high cost of growth medium necessary for cell growth. Mitogenic protein growth factors (GFs) are essential components of growth medium and account for upwards of 90% of the total costs. Here, we present a set of expression constructs and a simplified protocol for recombinant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Generally, 10∼20% of FBS in the media was considered suitable for cell culture, as reported in enterocytes 39 , stem cells 40 , and hybridoma 41 . Such a reduced amount of FBS was supposed to be a preferred trend, considering the risk of contamination, the cost, and the batch-to-batch variability in cell production 42, 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, 10∼20% of FBS in the media was considered suitable for cell culture, as reported in enterocytes 39 , stem cells 40 , and hybridoma 41 . Such a reduced amount of FBS was supposed to be a preferred trend, considering the risk of contamination, the cost, and the batch-to-batch variability in cell production 42, 43 .…”
Section: Resultsmentioning
confidence: 99%
“…As such, it is likely that process scale-up can drive down costs substantially by leveraging economies of scale. Methods to optimize and enhance recombinant growth factors or overcome their requirement in cell culture could also dramatically reduce these costs 8,[30][31][32][33] . Additionally, during Beefy-9 development, it was shown that lowering the concentration of FGF-2 to 5 ng/mL did not drastically reduce growth, and so this simple strategy could reduce the cost of Beefy-R to $21.7/L.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant DNA technology can then be used to insert sequences of interest into bacterial systems. Using this strategy, active GFs, such as FGF-2, IGFs, PDGF-BB, and TGF-β1 were effectively developed in Escherichia coli, and soluble GFs from cattle, chickens, and fish were produced [130].…”
Section: E T E D Animal Tissue Culture Techniquesmentioning
confidence: 99%